Awareness About Menstruation and Menstrual Hygiene Practices Among Adolescent Girls in Central India - Sanjay Dixit; Deepa Raghunath; Rahul Rokade; Syed Akbar Nawaz; Taruna Nagdeve; Ishu Goyal (Medsci Publications, 2016)
Background: Menstruation is a natural phenomenon unique to women and menstrual hygiene is fundamental to the wellbeing of women and girls. Objectives: To find the awareness about menstruation among ado- lescent girls in a government and private school and ascertain their menstrual hygiene practices. Methods: A cross sectional study was done on 100 girls between age of 12-16 years studying in a government school and a private school, after taking consent from the authority in charge. A self- administered, semi-structured, pre-tested questionnaire was used to find out Socio Demographic profile, Knowledge of menstrua- tion and Practices during menstruation. Chi square test with Yates correction was applied. Results: Mother was the first informant regarding menstruation in case of 70% of girls with 54% in government school and 86% girls in private school. For genital cleaning purpose 44% girls used both soap and water with 60% girls from government school and 28% from private school and 56% girls used plain water. Sanitary pads were used among 98% girls out of which 38% girls used the absor- bent material for 6-12 hours in which 50% belonged to private school and 16% belonged to government school. Conclusion: Awareness was higher and better menstrual hygiene was seen in the private school as compared to government school.